Wideband Flat Radomes Using Inhomogeneous Planar Layers - Mohammad Khalaj-Amirhosseini (International Journal of Antennas and Propagation)
Inhomogeneous planar layers (IPLs) are optimally designed as flat radomes in a desired frequency range. First, the electric permittivity function of the IPL is expanded in a truncated Fourier series. Then, the optimum values of the coefficients of the series are obtained through an optimization approach. The performance of the proposed structure is verified using some examples.